Compreensões históricas das disciplinas de Estágio Curricular Supervisionado no curso de Licenciatura em Matemática da UFMG (1968 - 1994) - Mariana Lima Vilela (2020)
In this dissertation we present, in a historical perspective, the subjects of Supervised Curricular Internship in the Mathematics Degree course at the Federal University of Minas Gerais (UFMG). Generally, it is considered that it is in the internship that the future teacher will have his first contact with a professional dimension of pedagogical practice and will prepare to exercise his teaching career. Considering the importance of the internship in the training of teachers, this dissertation aims to develop historical understandings of the disciplines of Supervised Curricular Internship at UFMG and their roles in the training of mathematics teachers. We use, as documentary sources, curricular grids, minutes of meetings, texts of seminars, menus, programs, class diaries and others. This study was carried out according to a qualitative approach, based on Micro-History elements in its theoretical and methodological basis. We took as a time frame the period between 1968, the year in which the University Reform took place, and 1994, when the first curriculum of the evening course in Mathematics at UFMG was approved, when an important curricular discussion took place, the last one registered before the Directives and Bases Law (LDB) of 1996. The main result of the research is the elaboration of historical understandings of the subjects of Supervised Curricular Internship from sources of the Institute of Exact Sciences (ICEx), of the Faculty of Education (FaE) and documents linked to teachers who taught the subjects, promoting highlights, approximations and divergences. In the ICEx discourse, the concern with teacher training is noted by the number of proposals and curricular reforms that have taken place, with the Institute's role being to prepare students exclusively for mathematical content, with the internship in charge of FaE. At different times, the FaE demonstrated the need to create subsidies to guide the execution and to establish a policy for the supervised curricular internship in undergraduate courses. Despite the problems that covered the subjects, we understand that the teachers believed and provided a training for Mathematics teachers focused on teaching practice, with spaces for the discussion of mathematical and pedagogical content, for observation, reflection and discussion of the practice, involving the intern in the school environment.